A History of the Afghan War (2001-2021) from a Defense Diplomacy Perspective - Hanggarini, Peni; Sambuaga, Theo; Anwar, Syaiful (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This paper discusses the asymmetric war in Afghanistan from 2001 to 2021 between the United States (US) and the Taliban from the perspective of defense diplomacy. The purpose of this paper is to identify assymetric war strategies and to evaluate defense diplomacy process to create peace. The research is based on qualitative method using secondary data from books, documents, and journals. The study indicates that defense diplomacy had succesfully led to the peace agreement, signed in Doha on February 29, 2020 between the US and the Taliban, which had been in conflict for nearly 20 years. However, the peace creation process is not easy due to the inhibiting factors which play more significant role than the supporting factors for defense diplomacy. Although the US, a super power, is supported by the North Atlantic Treaty Organization (NATO), Pakistan and several other countries, it is not a guarantee for the US to achieve its war objectives. The US goals and strategy continuously changed over time and imprecise in its implementation. The US’s failure to understand the political entity of the Taliban, particulary in the political, social and cultural aspects, is the main obstacle to achieving the US’ war goals and the ease implementation of defense diplomacy.